Evaluation of temperament of Hungarian Merino and German Blackheaded ewes and its relationship with some fertility traits - Pajor, Ferenc; Szenléleki, Andrea; Láczó, Edina; Rupcsó, Magdolna; Póti, Péter (Animal welfare, Ethology and Housing Systems (AWETH), 2007)
Authors measured temperament of twenty-five Hungarian Merino and ten German Blackheaded mother ewe by the scale test at weaning (temperament score: assessing behaviour of animals in a five-points scale, while spending 30 seconds on the weighing scale: 1: calm, no movement, 2: calm with occasional movements, 3: calm with some more movements without shaking the scale, 4: abrupt episodic movements without shaking the scale, 5: permanent episodic movements and shaking the scale) by two independent judges.Mother ewes were originated from Törtel. Average age of Hungarian Merino ewes was 4.2 year, average body weight was 65.2, their temperament score was 1.52, their total number of yeaned lambs was 9.5, their average number of yeaned lambs were 1.81, and their reproduction rate were 168%. In case of German Blackheaded ewes average age was 4.4 year, average body weight was 71.0, temperament score was 1.38, total number of yeaned lambs was 5.6 and average number of yeaned lambs was 1.65.Pregnancy ratio of the ewes with calm temperament was 173%, their weaned litter weight was 34.2 kg and body weight was 66.3 kg.Moreover, mothers with twin lambs were calmer, than mothers with single lamb in Hungarian Merino ewes. With growing of the age of mother and number of yeaned the mothers became calmer and had lower temperament score.The results showed that calm ewes had greater body weight, pregnancy ratio and litter weight than nervous ewes.
Keywords: sheep (Hungarian Merino, German Blackheaded); temperament; mother traits; reproduction performance